POLITENESS OF COMMUNICATION THAT DELIGHTS AND EMPOWERS STUDENTS AT MADRASAH IBTIDAIYAH - Fitri Puji Puji Rahmawati; Efi Rusdiyani (JPSD (Jurnal Pendidikan Sekolah Dasar), 2019)
Abstract. Language is the most important thing used in communication activities, the use of appropriate, correct, and good language can facilitate the delivery of information. School is a place where communication often occurs. The communication used in the school environment must be child friendly. Child-friendly language is a language that is used by looking at the child development. The research subjects used were the students of MI Muhammdiyah PK Kartasura. This research used a qualitative research methods. Data collection techniques using interview, observation, and documentation. The results of the research showed that in habituation activities, students imitated the teacher's attitude in communicating by greeting and using good language. The use of greetings in communicating with both students and teaching staff is also applied. The result of this habituation is that MI Muhammadiyah PK Kartasura students have the ability to behave and communicate well to teachers, students, and the school community as well. Keywords: politeness, communication, fun, child friendly